Dinamika Luas Panen dan Harga Komoditas terhadap Nilai Tukar Petani Subsektor Tanaman Pangan di Provinsi Sulawesi Tengah: Analisis Time Series - Ayu Cahya Ningsih; Sri Mardiyanti; Amruddin Amruddin; Mohammad Natsir (LPPM Institut Pendidikan Nusantara Global, 2025)
This study examines the influence of harvested area and commodity prices on the Farmers’ Terms of Trade (NTP) in Central Sulawesi, a region where fluctuations in agricultural production significantly affect farmers’ welfare. The topic is considered important because NTP is widely used as an indicator of farmers’ purchasing power and economic resilience, while changes in harvested area and commodity prices often create instability in income and production outcomes. Using a quantitative research design with time-series data, the study analyzes the relationship between harvested area, commodity prices, and NTP over the 2024 period. Regression analysis was employed to determine the magnitude of influence of each variable and to quantify how much of the variation in NTP can be explained by these factors. The results show that both harvested area and commodity prices have a significant positive effect on NTP, with an R-squared value of 0.82, indicating that 82% of the variation in NTP is explained by these variables. However, a 7.1% decline in harvested area in 2024 led to a decrease in NTP from 102.45 to 98.21, despite a 4–5% increase in the prices of rice and corn. The rise in commodity prices was insufficient to offset the increasing production costs, resulting in a decline in farmers’ purchasing power. These findings highlight the vulnerability of farmers to production shocks and price fluctuations, emphasizing the need for policies that stabilize input costs, support productivity improvements, and strengthen farmers’ economic resilience.